Development of a novel bioengineered 3D brain‐like tissue for studying primary blast‐induced traumatic brain injury. Issue 1 (6th October 2022) - Snapper, Dustin M.; Reginauld, Bianca; Liaudanskaya, Volha; Fitzpatrick, Vincent; Kim, Yeonho; Georgakoudi, Irene; Kaplan, David L.; Symes, Aviva J.
Abstract: Primary blast injury is caused by the direct impact of an overpressurization wave on the body. Due to limitations of current models, we have developed a novel approach to study primary blast‐induced traumatic brain injury. Specifically, we employ a bioengineered 3D brain‐like human tissue culture system composed of collagen‐infused silk protein donut‐like hydrogels embedded with human IPSC‐derived neurons, human astrocytes, and a human microglial cell line. We have utilized this system within an advanced blast simulator (ABS) to expose the 3D brain cultures to a blast wave that can be precisely controlled. These 3D cultures are enclosed in a 3D‐printed surrogate skull‐like material containing media which are then placed in a holder apparatus inside the ABS. This allows for exposure to the blast wave alone without any secondary injury occurring. We show that blast induces an increase in lactate dehydrogenase activity and glutamate release from the cultures, indicating cellular injury. Additionally, we observe a significant increase in axonal varicosities after blast. These varicosities can be stained with antibodies recognizing amyloid precursor protein. The presence of amyloid precursor protein deposits may indicate a blast‐induced axonal transport deficit. After blast injury, we find a transient release of the known TBI biomarkers, UCHL1 and NF‐H at 6 h and a delayed increase in S100B at 24 and 48 h. This in vitro model will enable us to gain a better understanding of clinically relevant pathological changes that occur following primary blast and can also be utilized for discovery and characterization of biomarkers. Abstract : In vitro tissue engineering provides a novel approach to investigate the cellular and molecular effects of traumatic brain injury. Here, we describe a bioengineered 3D brain‐like human tissue culture system to study primary blast‐induced traumatic brain injury.